2007
DOI: 10.1007/s00299-007-0402-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression pattern of rubber elongation factor (REF) mRNA transcripts from high and low yielding clones of rubber tree (Hevea brasiliensis Muell. Arg.)

Abstract: In Hevea tree, rubber elongation factor (REF) is a key gene involved in rubber biosynthesis. Since the immaturity period for Hevea is 6 years, identification of molecular marker for latex yield potential will be beneficial for early selection of high yielding clones. The main objective of this research is to study the expression pattern of the REF gene in contrasting latex yield rubber clones (high and low yielding) by Northern blot as well as RT-PCR analysis. Accumulation of REF mRNA transcripts was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 11 publications
2
39
0
Order By: Relevance
“…REF1 might contribute to rubber biosynthesis by facilitating the biogenesis of LRPs or the 'growing' of SRPs to LRPs. Two pieces of evidence support this presumption: (1) the amount of REF1 protein in the whole latex has been found to be proportional to the rubber content 26 ; (2) REF1 gene expression was reported to correlate with yield levels of Hevea cultivars 27 . Taking a hypothetical stance, if REF had not evolved to facilitate the formation of LRPs, the typical tapped latex that has a dry rubber content (drc) of 33% would have less than 3% drc for the same number of SRPs per unit volume.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…REF1 might contribute to rubber biosynthesis by facilitating the biogenesis of LRPs or the 'growing' of SRPs to LRPs. Two pieces of evidence support this presumption: (1) the amount of REF1 protein in the whole latex has been found to be proportional to the rubber content 26 ; (2) REF1 gene expression was reported to correlate with yield levels of Hevea cultivars 27 . Taking a hypothetical stance, if REF had not evolved to facilitate the formation of LRPs, the typical tapped latex that has a dry rubber content (drc) of 33% would have less than 3% drc for the same number of SRPs per unit volume.…”
Section: Discussionmentioning
confidence: 64%
“…A close involvement of REF and SRPP in rubber synthesis has been proposed based on in vitro rubber biosynthesis assays 25,26 , and a positive correlation of REF expression with rubber yield 27 . Recent transgenic studies in Taraxacum brevicorniculatum 28,29 also reveal their essential role in rubber biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the LDAP genes and their SRPP counterparts are strongly induced in some plants in response to abiotic stress (Sookmark et al, 2002;Priya et al, 2007;Kim et al, 2010;Seo et al, 2010;Fricke et al, 2013) as well as ectopic application of abscisic acid, as indicated by the Arabidopsis eFP Browser microarray database (Winter et al, 2007). LDs are also known to be involved in lipid metabolism associated with pathogen infection (Herker and Ott, 2012;Murphy, 2012), and biochemical studies have shown a significant increase in TAG and neutral lipids in plants subjected to heat, cold, drought, and salt stress (Mueller et al, 2015;Tarazona et al, 2015).…”
Section: A Role For Ldaps During the Plant Stress Responsementioning
confidence: 99%
“…In LDAP-disrupted plant lines, however, there were no significant decreases in neutral lipid content, although ldap3-1 and ldap3-2 mutant lines did show modest increases in neutral lipid abundance ( Fig. 3C Prior studies revealed that LDAP genes are strongly induced during abiotic stress responses in a variety of plant species (Sookmark et al, 2002;Priya et al, 2007;Kim et al, 2010;Seo et al, 2010;Fricke et al, 2013), and more recent studies have shown that neutral lipid content, particularly TAG, is increased in response to cold or heat (Mueller et al, 2015;Tarazona et al, 2015). Given that LDAPs target to LDs (Figs.…”
mentioning
confidence: 94%
“…Previous studies showed that ethylene stimulates latex production (Coupé and Chrestin 1989) and jasmonic acid (JA) induces differentiation of lactiferous cells (Hao and Wu 2000). A recent study showed that treatment of bark with ethephon, an ethylene releaser, induced the expression of REF, and the transcript level of REF was correlated with latex yield (Priya et al 2007). The ethylene and JA signaling pathways have been intensively studied to explore the molecular mechanisms regulating laticifer differentiation and natural rubber metabolism.…”
Section: Ref-s (5′-ttg Ttt Cag Caa Ttc Gag Ct-3′) and Ref-a (5′-tca Amentioning
confidence: 99%